Poor prognostic subgroup in T3N0 stage IIA gastric cancer, suggesting an indication for adjuvant chemotherapy. Issue 2 (18th October 2014) - Imamura, Taisuke; Komatsu, Shuhei; Ichikawa, Daisuke; Kubota, Takeshi; Okamoto, Kazuma; Konishi, Hirotaka; Shiozaki, Atsushi; Fujiwara, Hitoshi; Morimura, Ryo; Murayama, Yasutoshi; Kuriu, Yoshiaki; Ikoma, Hisashi; et al.
<x xml:space="preserve">Abstract</x> Background Adjuvant chemotherapy following curative gastrectomy is recommended for patients with pStage II or III, except pT3 (ss), N0 gastric cancer in Japan. This study aimed to detect the poor prognostic subgroup of T3N0 gastric cancer, suggesting an indication for adjuvant chemotherapy. Methods Between 1999 and 2011, 116 patients with pStage IIA gastric cancer underwent curative gastrectomy. We reviewed their hospital records retrospectively. Results The 5‐year overall survival (OS) rates of patients with T1N2 + T2N1 and T3N0 gastric cancer were 79% and 77%, respectively. Univariate and multivariate analyses revealed lymphatic invasion (LY+) to be an independent poor prognostic factor in T3N0 gastric cancer [P = 0.004, HR 12.3 (95% CI: 2.07–112)]. The prognosis of patients with T3N0LY+ gastric cancer was significantly poorer than those with other pStage IIA gastric cancer (5‐year OS; T3N0LY+ vs. other Stage IIA: 68% vs. 83%, P = 0.043). The incidence of peritoneal recurrence was higher in patients with T3N0LY+ gastric cancer than in those with other Stage IIA gastric cancer (T3N0LY+ vs. other stage IIA: 9.0% vs. 2.8%, P = 0.134). Conclusions Lymphatic invasion was an independent poor prognostic factor in T3N0 gastric cancer. Adjuvant chemotherapy should be recommended to patients with T3N0LY+ gastric cancer. J. Surg. Oncol. 2015 111:221–225. © 2014 Wiley Periodicals, Inc.